Advancements in Nanomedicine for Multiple Myeloma. Issue 6 (June 2018) - Detappe, Alexandre; Bustoros, Mark; Mouhieddine, Tarek H.; Ghoroghchian, P. Peter
Abstract : In the past decades, considerable progress has been made in our understanding and treatment of multiple myeloma. Several challenges remain including our abilities to longitudinally image tumor responses to treatment, to combine various therapeutic agents with different mechanisms of action but with overlapping toxicities, and to efficiently harness the power of the immune system to augment remission and/or to induce permanent cures. Nanomedicine may help to address many of these outstanding issues, affording novel diagnostic capabilities and offering disruptive technologies that promise to revolutionize treatment. Here, we review recent developments and the future of nanomedicine for multiple myeloma, highlighting new considerations in nanoparticle designs that may help to augment active targeting, to facilitate longitudinal imaging, and to improve drug delivery. Highlights: Targeted technologies enable specific binding of malignant plasma cells both in clinical samples and throughout the body of a patient. Nanomedicines may be used to improve diagnostic imaging by enhancing the sensitivity and specificity of existing contrast agents for malignant plasma cells. Nanomedicines can be used to facilitate the delivery of small molecules and macromolecular agents into the bone marrow microenvironment to augment antitumor responses.